2016
DOI: 10.1055/s-0042-100718
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-functional evaluation of small bowel using wireless motility capsule and video capsule endoscopy in patients with known or suspected Crohn’s disease: pilot study

Abstract: Background and study aims: SmartPill® (Given Imaging Corp.,Yoqneam,Israel) is an ingestible, non-imaging capsule that records physiological data including contractions and pH throughout the gastrointestinal tract. There are scarce data looking at SmartPill® assessment of patients with known/suspected small-bowel Crohn’s Disease (CD). This pilot study aims to investigate feasibility and safety of SmartPill® to assess gut motility in this group.  Patients and methods: Over 1 year, patients with known/suspected C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Our VCE GET values are similar to those of healthy subjects reported by others, including a recent study in which both WMC and VCE were performed in the same healthy subjects on same visit . In the latter paper, mean VCE GET was 73 min (personal communication from D. Yung); mean WMC GET was 250 min.…”
Section: Discussionmentioning
confidence: 99%
“…Our VCE GET values are similar to those of healthy subjects reported by others, including a recent study in which both WMC and VCE were performed in the same healthy subjects on same visit . In the latter paper, mean VCE GET was 73 min (personal communication from D. Yung); mean WMC GET was 250 min.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Farmer et al 35 stated that WMC testing is contraindicated in IBD patients with known or suspected strictures along the length of the GI tract. However, even more recently, Yung et al 40 reported results from the first pilot study on a morphofunctional evaluation of the small bowel using a WMC and WCE in patients with known or suspected CD. In the respective study, they had administered the PillCam SB2, a WCE, and the SmartPill to 12 CD patients and 33 controls.…”
Section: Acquisition Of Appropriate Gi Transit Profilesmentioning
confidence: 99%
“…Common symptoms of CD and UC are abdominal pain, diarrhea, and rectal bleeding. Patients with IBD display abnormal motility of the small intestine ( 13 , 14 , 15 , 16 ) and colon ( 17 , 18 , 19 ). Figure 1
Fig.
…”
Section: Pathophysiological Features Of Icc In Inflammatory Diseasementioning
confidence: 99%